2021
DOI: 10.1039/d1nj02148f
|View full text |Cite
|
Sign up to set email alerts
|

Metal-doped carbon nitrides: synthesis, structure and applications

Abstract: Doping of metal is a common strategy to regulate the structure of carbon nitride materials at the molecular level. A wide range of intriguing applications of metal-doped carbon nitride (M-CN)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 92 publications
0
25
0
Order By: Relevance
“…[92] According to past studies, pyridinic N contributes with four electrons to the sp 2 configuration with a lone pair, while the other valence electron exists in the π-conjugated system. [22,27,93] Owing to the higher electronegativity of a nitrogen atom compared to that of a carbon atom, the pyridinic N is negatively charged, as proved by the aforementioned experiment related to the Lewis base. [22,27,94] On the other hand, by measuring the electrocatalytic performances of a series of electrocatalysts with different types of N species, Yang et al showed that the electron-donating graphitic N served as ORR active centers, whereas the electron-withdrawing functional groups acted as OER active centers.…”
Section: Nitrogen Atoms As Electrocatalytic Active Sitesmentioning
confidence: 96%
“…[92] According to past studies, pyridinic N contributes with four electrons to the sp 2 configuration with a lone pair, while the other valence electron exists in the π-conjugated system. [22,27,93] Owing to the higher electronegativity of a nitrogen atom compared to that of a carbon atom, the pyridinic N is negatively charged, as proved by the aforementioned experiment related to the Lewis base. [22,27,94] On the other hand, by measuring the electrocatalytic performances of a series of electrocatalysts with different types of N species, Yang et al showed that the electron-donating graphitic N served as ORR active centers, whereas the electron-withdrawing functional groups acted as OER active centers.…”
Section: Nitrogen Atoms As Electrocatalytic Active Sitesmentioning
confidence: 96%
“…Considering the future development of the 2D/2D vdW heterostructure, switching to new carbon nitride-based materials is essential to fully cultivate the benefits of 2D/2D configuration. Molecular engineering by doping (nonmetal, alkali metal, and single atoms), alteration of the coordination pattern (bridging N, C atoms, or azo linkages), insertion of N-rich units such as triazole units, and replacing the basic triazine/heptazine units with new construction units are some fundamental strategies to advancing the intrinsic physicochemical properties of carbon nitrides. , Several new variants of the C x N y family with an entirely different stoichiometric C:N ratio such as C 2 N, C 3 N, C 3 N 2 , C 3 N 3 , C 4 N 3 , C 3 N 5 , and C 3 N 6 and novel photophysical behavior have been synthesized in recent years to conquer the drawbacks of conventional C 3 N 4 . ,,, Another grueling issue with carbon nitride-based 2D/2D heterojunctions is the indigent surface adsorption of the reactant and poor adsorption–desorption kinetics. Surface engineering of carbon nitride by introducing certain functional groups/units with a high affinity for reactants can solve this problem.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…31 Through doping with foreign atoms into carbon matrices, new stable defect sites with strong anchoring ability to metal atoms can be created. [32][33][34] In this context, highly efficient single-atom Pt catalysts hosted on carbon nitride have been constructed, which exhibited outstanding performance in photocatalytic H 2 evolution. [35][36][37] In this paper, single Pt atom catalysts with different coordination atoms (N, and/or O) were prepared by adopting two carbonaceous carriers i.e., N-doped carbon (NC) and graphitic carbon nitride (C 3 N 4 ).…”
Section: Introductionmentioning
confidence: 99%